Wideband Ge-Rich SiGe Polarization-Insensitive Waveguides for Mid-Infrared Free-Space Communications - Vladyslav Vakarin; Joan Manel Ramírez; Jacopo Frigerio; Qiankun Liu; Andrea Ballabio; Xavier Le Roux; Carlos Alonso-Ramos; Giovanni Isella; Pavel Cheben; Winnie N. Ye; Laurent Vivien; Delphine Marris-Morini (Applied Sciences, 2018)
The recent development of quantum cascade lasers, with room-temperature emission in the mid-infrared range, opened new opportunities for the implementation of ultra-wideband communication systems. Specifically, the mid-infrared atmospheric transparency windows, comprising wavelengths between 3–5 µm and 8–14 µm, have great potential for free-space communications, as they provide a wide unregulated spectrum with low Mie and Rayleigh scattering and reduced background noise. Despite the great efforts devoted to the development of mid-infrared sources and detectors, little attention is dedicated to the management of polarization for signal processing. In this work, we used Ge-rich SiGe alloys to build a wideband and polarization-insensitive mid-infrared photonic platform. We showed that the gradual index change in the SiGe alloys enabled the design of waveguides with remarkably low birefringence, below 2 × 10−4, over ultra-wide wavelength ranges within both atmospheric transparency windows, near wavelengths of 3.5 µm and 9 µm. We also report on the design of a polarization-independent multimode interference device achieving efficient power splitting in an unprecedented 4.5-µm bandwidth at around 10-µm wavelength. The ultra-wideband polarization-insensitive building blocks presented here pave the way for the development of high-performance on-chip photonic circuits for next-generation mid-infrared free-space communication systems.